2011
DOI: 10.1016/j.jcrs.2011.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous bilateral versus sequential bilateral cataract surgery: Helsinki Simultaneous Bilateral Cataract Surgery Study Report 1

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
129
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(144 citation statements)
references
References 48 publications
11
129
0
4
Order By: Relevance
“…7,14 Evidence-based clinical and policy decisions on the choice of operative technique require more robust scientific knowledge about safety, effectiveness, and cost effectiveness. One recent clinical trial 15 and 1 economic analysis 16 support the previous findings in several case series. [3][4][5][6][7][8][9][10][11] These studies found that patients treated with ISBCS recovered visual function faster with no increase in the risk for relevant complications.…”
mentioning
confidence: 54%
“…7,14 Evidence-based clinical and policy decisions on the choice of operative technique require more robust scientific knowledge about safety, effectiveness, and cost effectiveness. One recent clinical trial 15 and 1 economic analysis 16 support the previous findings in several case series. [3][4][5][6][7][8][9][10][11] These studies found that patients treated with ISBCS recovered visual function faster with no increase in the risk for relevant complications.…”
mentioning
confidence: 54%
“…7 However, it still remains quite controversial 3,8 as one of the main reasons is risk of bilateral endophthalmitis, which could lead to bilateral visual loss. The reported incidence of endophthalmitis following simultaneous bilateral cataract surgery is between 0.15 and 1.1%, as compared with 0.1% or less following unilateral or sequential cataract extractions.…”
Section: Discussionmentioning
confidence: 99%
“…7 Furthermore, the visual benefit of same-day surgery is also short-lived and by 4 months there is no significant difference between ISCS and sequential surgery with a 2-month interval. 5 If it can be determined whether patients are happy to wait until the success of the first-eye surgery, it would seem prudent to do so.…”
mentioning
confidence: 98%
“…5 With appropriate case selection 6 and precautions against endophthalmitis and refractive surprise, ISCS can result in excellent outcomes and high levels of patient satisfaction. 1,7,8 Despite growing interest, in most countries ISCS remains the exception rather than the rule, and it is our view that it should remain this way and that bilateral cataract surgery should not be routinely offered to patients. The arguments in favour of same-day bilateral surgery are primarily related to convenience and economy, 9 but these benefits are outweighed in most circumstances by the small but devastating risk of bilateral blindness due to a complication of surgery.…”
mentioning
confidence: 99%